Text Complexity in An Indonesian EFL Textbook: Is it Aligned with the Emancipated Curriculum Goals? - Istihari Istihari; Yudi Juniardi; Vivi Sofiah; Yanwar Abidin (English Department - University of Sultan Ageng Tirtayasa, 2025)
This study examines the textual complexity of an Indonesian EFL textbook under the Emancipated Curriculum, focusing on lexical density and grammatical intricacy. Ten reading passages from the 10th-grade textbook Bahasa Inggris Work in Progress were analyzed using Halliday’s framework for lexical density and Eggins & Castello’s framework for grammatical intricacy. The findings reveal a lexical density index of 5.67 and a grammatical intricacy index of 1.78, indicating moderate textual complexity. The moderate lexical density and grammatical intricacy reflect a balance of accessibility and challenge, suitable for senior high school students where English becomes a foreign language. However, the complexity may not fully meet the needs of advanced learners. These findings contribute to discussions on curriculum effectiveness and reading comprehension, offering insights for teachers to select and adapt materials based on students’ proficiency levels and learning needs.